Collagen content and extracellular matrix cause cytoskeletal remodelling in pancreatic fibroblasts. Issue 154 (31st May 2019) - Stylianou, Andreas; Gkretsi, Vasiliki; Louca, Maria; Zacharia, Lefteris C.; Stylianopoulos, Triantafyllos
Abstract : In many solid tumours a desmoplastic reaction takes place, which results in tumour tissue stiffening due to the extensive production of extracellular matrix (ECM) proteins, such as collagen, by stromal cells, mainly fibroblasts (FBs) and cancer-associated fibroblasts (CAFs). In this study, we investigated the effect of collagen stiffness on pancreatic FBs and CAFs, particularly on specific cytoskeleton properties and gene expression involved in tumour invasion. We found that cells become stiffer when they are cultured on stiff substrates and express higher levels of alpha-smooth muscle actin (α-SMA). Also, it was confirmed that on stiff substrates, CAFs are softer than FBs, while on soft substrates they have comparable Young's moduli. Furthermore, the number of spread FBs and CAFs was higher in stiffer substrates, which was also confirmed by Ras-related C3 botulinum toxin substrate 1 ( RAC1 ) mRNA expression, which mediates cell spreading. Although stress fibres in FBs become more oriented on stiff substrates, CAFs have oriented stress fibres regardless of substrate stiffness. Subsequently, we demonstrated that cells' invasion has a differential response to stiffness, which was associated with regulation of Ras homologue family member ( RhoA ) and Rho-associated, coiled-coil containing protein kinase 1 ( ROCK-1 ) mRNA expression. Overall, our results demonstrate that collagen stiffness modulates FBs and CAFs cytoskeleton remodelling and alters their invasion properties.